Determinants of Corporate Financial Factors on Tax Reporting Strategy - Valipour, Hashem; Homayoun, Saeid; Piran, Fateme (International Journal of Economics and Financial Issues, 2017)
The primary objective of present study is to analyze the effects of financial factors on financial and tax reporting decisions. The statistical population of present study includes all companies listed in Tehran Stock Exchange out of which 438 companies are included in the statistical sample of present study. The results suggests that there is a significant positive association between debt ratio and aggressive financial reporting. In addition, there is a significant negative association between debt ratio and aggressive tax reporting. Keywords: Debt Ratio, Long-term Debt Ratio, Aggressive Financial Reporting, Aggressive Tax Reporting. JEL Classifications: M4; H25; H2